Teenage Taboo Jargons among High Schoolers and Undergraduates - Alemina Br Perangin-angin; Meliana Siboro; Ade Namira (Talenta Publisher, 2022)
The dynamic of language can be seen from the constant emergence of new vocabulary, which mainly spread among teenagers. Swearing, cursing, and other taboo words are daily among teenagers. Compared to the previous generation, like those born in the 90s, the prominent use of taboo words is now more evident. This study investigated how the benefits of swear terms among high schoolers differ from undergraduate students. Data were collected through direct online interviews via Zoom call. Each participant was asked about the frequently used swear words and their reasons. The data were presented in the qualitative descriptive method. The result showed that high school students use swear words relating to sexuality, animal terms abuse, sexist terms abuse, intellect-based terms abuse, insult, and slur, while college students used the same categories of swear words, except sexist terms abuse. Accordingly, high school students used swear words to show they were mature enough, such as self-expression, humor, social bonding among friends, and a new normal in teenagers’ lives. Meanwhile, college students used swear words as humor, self-expression, and pain relief.